Poverty reduction and human resource development in the Caribbean - Baker, Judy L. (World Bank [Washington]US, 1996)
Seeks to improve our understanding of poverty in the Caribbean and the current efforts to address it, with the aim of identifying how policies and programmes can be more effective.